2021
DOI: 10.3390/medicina57080749
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Cancer: Current Challenges and Future Directions

Abstract: Bladder cancer (BCa) is the most common malignancy of the urinary tract and one of the most prevalent cancers worldwide. While the clinical approach to BCa has remained largely unchanged for many years, recent discoveries have paved the way to a new era of diagnosis and management of the disease. BCa-specific mortality started to decrease in the regions with a wide range of activities leading to greater social awareness of the risk factors and the decline in carcinogenic exposure. The urologic community refine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
111
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(142 citation statements)
references
References 42 publications
0
111
0
2
Order By: Relevance
“…BC is a highly malignant cancer with a poor prognosis and remains difficult to treat [ 2 ]. Although multimodality treatments have allowed patients to live longer, treatment outcomes remain poor [ 25 ]. In addition, patients with similar clinical features may also present with different prognoses and responses to oncological treatment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BC is a highly malignant cancer with a poor prognosis and remains difficult to treat [ 2 ]. Although multimodality treatments have allowed patients to live longer, treatment outcomes remain poor [ 25 ]. In addition, patients with similar clinical features may also present with different prognoses and responses to oncological treatment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic assessment is critical for monitoring follow-up and treatment decisions in BC patients. At present, a variety of staging and grading systems based on the clinicopathological characteristics of patients are recommended in clinical practice guidelines, which have certain guiding significance for the management and prognostic risk assessment of BC patients [ 25 , 26 ]. However, these assessment methods still have limitations in the prognostic risk stratification of patients and cannot well distinguish the prognostic risk of patients with the same clinical stage or similar histological grades [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its incidence varies by region, with more than 60% of cases occurring in less developed countries ( 23 ). Approximately 75% of patients are diagnosed with non-muscle-invasive BLCA, while the remainder have already progressed to the muscle-invasive stage at diagnosis ( 24 ). Although new diagnostic and treatment strategies have recently been developed, only a minimal improvement in the clinical efficacy of these strategies has been reported ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer, as one of the common tumors of the urinary system, has a high incidence worldwide and the treatment of bladder cancer has been similar in the past. However, current advances in research on molecular and tumorigenic mechanisms have opened the door to personalized treatment of bladder cancer ( 9 ). Furthermore, in studies related to Necroptosis and bladder cancer, Wang et al found that induction of Necroptosis is another way to overcome apoptosis resistance in BC treatment ( 10 ).…”
Section: Introductionmentioning
confidence: 99%